Influence of tillage on physical properties and water holding capacity of the soil - HIRAPARA, PARAS; KATHIRIYA, GAURAV; SONAWANE, ASHISH V. (Journal of Soil and Water Conservation, 2022)
Tillage is one of the most important operations in agriculture. Tillage not only helps to provide favorablesoil conditions for plant growth but also improves the physical condition of the soil. It also affects themoisture holding capacity of the soil. An experiment to study the influence of various tillage operationson the physical properties and infiltration characteristics of soil indicated. It was observed that moisturecontent was highest in rotavator tilled soil (17.75%), and lowest in M.B. plough tilled soil (14.68%). Bulkdensity was found to be highest in M. B. plough (2.35 Mg m-3) while it was lowest in M. B. ploughed androtavator tilled soil (1.3935 Mg m-3. The infiltration rate was lowest in the undisturbed soil (0.01 cmmin-1) and was highest in the soil tilled with M. B. plough (0.1 cm min-1). The infiltration rate was higherin M.B. ploughed and rotavator tilled soil (0.09 cm min-1) as that of tilled by rotavator (0.03 cmmin-1). Itwas observed that seed germination was highest (90%) while lowest (85%) in rotavator tilled soil